Risk Assessment of Arsenic and Cadmium in Groundwater of Talukas Ghorabari and Mirpur Sakro, Sindh, Pakistan - Abdul Raheem Shar; Ghulam Qadir Shar; Shafi Muhammad Wassan; Zubeda Bhatti; Abida Ali Shar; Noor- ul-Hassan Shar (Pakistan Journal of Analytical & Environmental Chemistry, 2021)
The current study was carried out for quantitative and risk assessment of cadmium (Cd) and arsenic (As) from Talukas Ghora Bari and Mirpur Sakro. The concentration of Cd was determined using Atomic Absorption Spectroscopy instrument. The As concentration was measured with the help of the Arsenic Kit Method. For analysis of Cd, samples were prepared by the Microwave digestion method, whereas for As analysis, water samples were analyzed directly. The range of Cd content was observed from the studied areas as 1 – 10 µg/L and 1.2 – 11.2 µg/L, respectively. The groundwater water of Talukas Ghorabari and Mirpur Sakro showed the mean Cd content of 5 µg/L and 6.1 µg/L, respectively. The Cd contamination of 56% and 80% was found in Ghorabari and Mirpur Sakro, respectively. The range of As content of 0.00 – 50 µg/L and 10 – 80 µg/L was determined from Ghorabari and Mirpur Sakro, respectively. Hazard Quotient for Cd > 1 was found in 40% of both children and infants in the groundwater of the study area, which may cause non-carcinogenic risk. About 48% of water samples declared HQ values > 1 for adults in the water of Ghorabari. Since 84% of samples showed the HQ values > 1 for children and infants. The HQ values of As for Adults of the Mirpur Sakro were observed in 63.3% samples, whereas for children and infants, HQ values were found in 100% samples. It is therefore strongly recommended that groundwater must be treated before consumption by the people of the area under study.